Fillers - Flores Huicochea, Emmanuel (IntechOpen, 2021)
Fillers, in general, are substances that can be added to various polymer systems to reduce the cost or/and improve their physical-chemistry properties. Fillers can be either organic or inorganic, and added into the main matrix in different ways as a solid, liquid, or gas with different dimension scales, including macro, micro, even nanoscale. The aim of this book is to present the most updated information on the fillers in different application fields, such as wood adhesives, plastic, poly (lactic acid, PLA)/rubber composite, and packaging fields. In addition, the most recent research achievements of fillers in different fields will also be covered.